Evaluating 5.5 Years of Equinella: A Veterinary-Based Voluntary Infectious Disease Surveillance System of Equines in Switzerland - Özçelik, Ranya; Graubner, Claudia; Remy-Wohlfender, Franziska; Dürr, Salome; Faverjon, Céline (Frontiers in Veterinary Science, 2020)
Equine health is important in regards to trade, economy, society and the veterinary as well as public health. To reduce the burden of equine infectious diseases internationally it is important to collect, review and distribute equine health surveillance data as accurate and timely as possible. Within this study we aimed at providing a comprehensive descriptive analysis of data submitted to Equinella, a voluntary veterinary-based surveillance system of non-notifiable equine infectious diseases and clinical signs in Switzerland. This was achieved by reviewing reports submitted since its relaunch in November 2013 and until April 2019, as well as assessing the data validity, activeness of veterinarians, coverage of the equine population, geographical representativeness and timeliness of the system. In total 630 reports have been submitted. Data validity ranged between 88.2 to 100%. The coverage of Equinella was assessed to be 50.8 % of the Swiss equine population. Over the 5.5 years, of all 102 registered veterinarians, 67 (65.7%) submitted at least one report. On average, these veterinarians submitted 1.7 reports per year (median = 4 reports). More recently in 2018, only about one third (29, 28.4%) of all registered veterinarians submitted at least one report. However, 59 (57.8%) have responded to the monthly reminder e-mails to confirm that they have not observed any relevant clinical case at least once (median number of confirmation per veterinarian = 9 out of 12 reminder e-mails). The incidence of reports varied between cantons (member states of the Swiss confederation). The median timeliness of report submission was found to be 7 days. Overall, Equinella has been receiving reports since its initiation and contributed continuously to the surveillance of infectious diseases in the Swiss equine population and provided an output for the international equine community. Challenges encountered in achieving a higher number of submitted reports and increasing the coverage of the equine population as well as the overall activeness of veterinarians require further work. With our study we provide a comprehensive overview of a veterinary-based voluntary surveillance system for equine health, assessed challenges of such and suggest concrete improvements with transdisciplinary approaches for similar veterinary-based surveillance systems.